2020
DOI: 10.48550/arxiv.2011.04504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying effects of multiple treatments in the presence of unmeasured confounding

Abstract: Identification of treatment effects in the presence of unmeasured confounding is a persistent problem in the social, biological, and medical sciences. The problem of unmeasured confounding in settings with multiple treatments is most common in statistical genetics and bioinformatics settings, where researchers have developed many successful statistical strategies without engaging deeply with the causal aspects of the problem. Recently there have been a number of attempts to bridge the gap between these statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…In particular, under linear Gaussian structural equation models for at least three exposures, D'Amour (2019) and Ogburn et al (2019) showed that except in trivial cases, identification of the ACE is not possible without a parametric model for the outcome, while Kong et al (2019) further showed that the ACE is identifiable if one also assumes a parametric binary choice outcome model with a non-probit link. Alternatively, several authors have shown that identification is possible by collecting auxiliary variables such as instrumental variables or negative control outcomes (D'Amour, 2019; Imai and Jiang, 2019;Miao et al, 2020). In contrast to the multi-cause framework, under a conditional independence structure among multiple outcomes, we achieve nonparametric identification with at least three parallel outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, under linear Gaussian structural equation models for at least three exposures, D'Amour (2019) and Ogburn et al (2019) showed that except in trivial cases, identification of the ACE is not possible without a parametric model for the outcome, while Kong et al (2019) further showed that the ACE is identifiable if one also assumes a parametric binary choice outcome model with a non-probit link. Alternatively, several authors have shown that identification is possible by collecting auxiliary variables such as instrumental variables or negative control outcomes (D'Amour, 2019; Imai and Jiang, 2019;Miao et al, 2020). In contrast to the multi-cause framework, under a conditional independence structure among multiple outcomes, we achieve nonparametric identification with at least three parallel outcomes.…”
Section: Introductionmentioning
confidence: 99%